La materialización de lo simbólico: zonas de amortiguamiento - Patiño Núñez, Alberto (2025)
The artistic project “Buffer Zones” (2023) created by Erika Vásquez and Norka Uribe, aims to explore the relationships between the body, space and time in the current context of our city in order to, at the same time, propose a reflection on the official narratives of Peru of the last fifty years and their constitutive effects on the formation of the identities of the inhabitants of our country. The project is established as a questioning of these hegemonic narratives and, rather, proposes questions and reflections from unofficial spaces of the city’s memory, taking into account its material aspect and also from what seems ungraspable. The official/unofficial duality is addressed from its borders and liminal states in a proposal that builds from the extramural walls of our national history, materializing through various artistic forms, including sculpture, sound sculpture, ephemeral intervention in situ and video. This set of works, as we will see, invites us to question hegemonic narratives, proposing a rereading of the past and an invitation to critically reimagine the national present.